2015
DOI: 10.1016/j.jor.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Staged treatment of pilon fractures

Abstract: Staged anterolateral plating is superior to staged medial plating in the management of pilon fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
8
0
3
Order By: Relevance
“…The eight studies that met the inclusion criteria comprised one randomized controlled trial, one prospective cohort study, and six retrospective nonrandomized studies (Table 1). [9][10][11][12][13][14][15][16] The eight eligible studies involved 360 fractures in 359 patients. Of these 360 fractures, 175 were treated with two-stage ORIF and 184 were treated with LIFEF.…”
Section: Resultsmentioning
confidence: 99%
“…The eight studies that met the inclusion criteria comprised one randomized controlled trial, one prospective cohort study, and six retrospective nonrandomized studies (Table 1). [9][10][11][12][13][14][15][16] The eight eligible studies involved 360 fractures in 359 patients. Of these 360 fractures, 175 were treated with two-stage ORIF and 184 were treated with LIFEF.…”
Section: Resultsmentioning
confidence: 99%
“…They found a rate of healing of 88.13%, 3% with deep infection and 5% with superficial infection. 13 Deivaraju et al 14 analyzed the two-stage treatment, using a medial plate or an anterolateral plate during ORIF. They found comparable results in terms of quality of reduction and soft-tissue complications; however, they observed a higher incidence of infection and nonunion with medial plates.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 It is also important to appropriately handle the soft tissues. 9 There is some controversy in the literature regarding the variables affecting outcome in fractures of the tibial pilon treated by open reduction and internal fixation (ORIF): One stage (<48 h) 7,10,11 or two stages (staged treatment), placing an external fixator (EF) or a plaster splint in the first stage, delaying definitive ORIF until the soft tissues are healed, 8,9,[12][13][14] et cetera.…”
Section: Introductionmentioning
confidence: 99%
“…The reports vary however, with some authors favoring it [50] , while others not finding any advantage by its use [51] . A combination of an anteromedial with a lateral approach is usually preferred [40] , but Deivaraju et al [52] , found that overall, anterolateral plating was superior to medial plating in terms of bone healing complications. In addition, the routine use of locking plates in these injuries is questionable, as they do not seem to offer any advantage over non-locking plates [53] .…”
Section: Definitive Management Of Tibial Pilon Fracturesthe Evidencementioning
confidence: 99%